Fortress under Siege: Narratives of Ethnic Conflict and Discrimination among Hungarian Youth in Vojvodina - Krisztina Rácz (University of Belgrade, 2018)
This paper analyzes narratives of ethnic conflict among Hungarian and Serbian youth in Vojvodina. These experiences are narrated by Hungarian young people from Mali Iđoš in the Central Bačka region in the interviews with the author of the paper, and the excerpts of the transcripts are analyzed according to the Labovian socio-linguistic scheme. It argues that narrative structure varies according to the interlocutor’s gender; however, all narratives demonstrate similarity in terms of positioning the protagonists of such events as committing subjects and suffering objects. In addition, the narratives are highly script-like, which suggests a lack of diversity in the available discursive frames for narrating the experience of conflicts perceived as ethnically motivated. The most common script, which the interlocutors of this research use as well, constructs and justifies ethnic groups as simultaneously in confrontation with and isolated from each other, linguistically, culturally and geographically, and articulates interethnic experiences as a threat.